Pengembangan Media Pembelajaran Calistung Pada Anak Usia 4 – 6 Tahun Berbasis Android - R. Yadi Rakhman Alamsyah; Marwondo Marwondo; Iqbal Maulana (Ma'soem University, 2023)
Multimedia-based learning media is one of the essential tools in supporting the learning process, especially for early childhood education, such as children aged 4-6 years old. The issue with conventional teaching methods is the lack of visualization during material delivery, which hinders the effectiveness of the teaching and learning process. This leads to a decrease in children's interest and a sense of boredom during the learning process. The utilization of multimedia-based literacy learning media in the teaching and learning process can greatly assist in delivering educational materials in a more engaging and interactive manner. This is because multimedia-based learning media is equipped with features such as images, sound, text, and animations that enhance children's learning experiences in understanding the subject matter. Furthermore, multimedia-based learning media can also help reduce boredom levels among children during the teaching and learning process. This is because children are more likely to engage and stay focused on the learning process when they use interesting and interactive media. The development method of multimedia drills and practice used by the author in creating multimedia-based literacy learning media is highly effective. This method allows children to practice and review the subject matter repeatedly until they truly understand and master it. Overall, the utilization of multimedia-based learning media in literacy education can provide numerous benefits for children aged 4-6 years old. This media can enhance children's learning experiences in understanding educational materials, expedite the learning process, and help reduce boredom levels among children during the learning process. Therefore, it is essential for educators to leverage multimedia-based learning media as a tool to enhance the quality of education for early childhood learners.